Managing industrial service offerings: requirements on content and processes. (6th January 2009) - Kowalkowski, Christian; Brehmer, Per-Olof; Kindstrom, Daniel
This paper develops a typology for industrial service offerings, inter-relating service scope (degree of bundling), service focus (level of customer integration) and service process interfaces. Different forms of industrial services and the impact of information and communication technology on the three service dimensions are discussed, and requirements are identified related to the expansion of services. It is suggested that bundled and process-orientated services hold a major potential for manufacturing companies and can facilitate the creation of competitive advantage and long-term relationships with customers. Increased knowledge of the customers' installed base and business processes enables better customisation of the service offerings. Even if more emphasis is put on standardising and formalising central and local processes, companies need to recognise local differences among subsidiaries.